Brain glutathione levels and age at onset of illness in chronic schizophrenia. Issue 6 (27th December 2019) - Yang, Yvonne S.; Maddock, Richard J.; Lee, Junghee; Zhang, Huailin; Hellemann, Gerhard; Narr, Katherine L.; Marder, Stephen R.; Green, Michael F.
Abstract: Objective: Oxidative stress is implicated in the aetiology of schizophrenia, and the antioxidant defence system (AODS) may be protective in this illness. We examined the major antioxidant glutathione (GSH) in prefrontal brain and its correlates with clinical and demographic variables in schizophrenia. Methods: GSH levels were measured in the dorsolateral prefrontal region of 28 patients with chronic schizophrenia using a magnetic resonance spectroscopy sequence specifically adapted for GSH. We examined correlations of GSH levels with age, age at onset of illness, duration of illness, and clinical symptoms. Results: We found a negative correlation between GSH levels and age at onset ( r = −0.46, p = 0.015), and a trend-level positive relationship between GSH and duration of illness ( r = 0.34, p = 0.076). Conclusion: Our findings are consistent with a possible compensatory upregulation of the AODS with longer duration of illness and suggest that the AODS may play a role in schizophrenia.